Early recovery after surgery for radical cystectomy: comprehensive assessment and meta-analysis of existing protocols - Wessels, Frederik; Lenhart, Maximilian; Kowalewski, Karl-Friedrich; Braun, Volker; Terboven, Tom; Roghmann, Florian Bernhard Gerhard; Michel, Maurice Stephan; Honeck, Patrick; Kriegmair, Maximilian (World journal of urology, 2020)
Different enhanced recovery after surgery (ERAS) protocols (EP) for radical cystectomy (RC) have been published. Protocols highly differ in number of included items and specific measures.